FORMULASI GEL EKSTRAK DAUN SASALADAHAN (PEPEROMIA PELLUCIDA (L.) H.B.K) DAN UJI EFEKTIVITASNYA TERHADAP LUKA BAKAR PADA KELINCI (ORYCTOLAGUS CUNICULUS) - Mappa, Tiara; Edy, Hosea Jaya; Kojong, Novel (PHARMACON, 2013)
Sasaladahan contains saponin, tannin, alkaloid, calcium oxalate, fat, essential oil, flavonoid,steroid, triterpenoid and carbohydrate. Saponin can stimulate the formation of collagen, whiletannin and flavonoid have activity as antiseptic and antibacterial. The aims of this researchwere to determine the quality of Sasaladahan leaves extract gel (Peperomia pellucida (L.)HBK) by varying the concentration of 5%, 10% and 15% and its effect on the healing of burnwound. The quality of gel was test with organoleptic test, homogenity, pH, spreadability andconsistency. The effectiveness test of the gel performed on 5 rabbits were divided into 5treatment groups where each rabbit made 3 burn wound using a hot metal plate with diameterof 20 mm. The first rabbit was given sasaladahan gel with a concentration of 5%, 2nd rabbitgiven sasaladahan gel with a concentration of 10%, 3rd rabbit given sasaladahan gel with aconcentration of 15%, 4th rabbit given a positive control and 5th rabbit given a negativecontrol. The wound diameter be measured every day until day 7. Data were statisticallyanalyzed using One Way Anova. The results show Sasaladahan gel with concentration of 5%,10% and 15% fulfilled the parameter evaluation of organoleptic test, homogenity, pH andconsistency while the results of spreadability test are not yet fulfilled the parameter of a goodspreadability (5-7 cm). The result of the effectiveness test of Sasaladahan leaves extract gelshow sasaladahan leaves extract gel with concentration of 5%, 10% and 15% have thehealing effect on burn wound.Keywords: Gel, Extract, Sasaladahan Leaves, Burn wound, Rabbit